Hukum Islam Perspektif Politik Penyelenggaraan Pemerintahan Indonesia - Mannang, Abd.; R, Rahmatiah; Akmal, Andi; Alwaris, Sri Ayu Andari Putri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This journal discusses the relationship between Islamic law and politics in the organization of Indonesian government. As a country with a Muslim majority population, Indonesia has its own challenges in integrating Islamic values in a democratic and pluralistic system of governance. Through a normative and juridical approach, this article analyzes the position of Islamic law in the national legal system, the political implications of its application, as well as the role of Islamic political actors in shaping public policy. This study demonstrates that Islamic law does not stand as a separate legal system, yet contributes to the formation of national law through a democratic political process. The interaction between Islamic law and state politics suggests the existence of a dynamic of adaptation and negotiation in maintaining a balance between religious values and principles of nationality.